Socially Responsible Investing: An Investor Perspective - Berry, Thomas C.; Junkus, Joan C. (2013)
Given the growing importance of Socially Responsible Investing (SRI), it is surprising that there is no consensus of what the term SRI means to an investor. Further, most studies of this question rely solely on the views of investors who already invest in SRI funds. Our study surveys a unique pool of approximately 5,000 investors that contains both investors who have used SRI criteria in investment decisions and those who have not, and involves a broad array of criteria associated with SR investing. Our findings offer new insight into the SRI debate. For both sets of investors, environmental and sustainability issues dominate as the major category associated with SR investing. We find strong agreement in the ranking of the relative importance of various SRI factors despite differences between these two groups in their opinion of their overall importance. We also find that investors prefer to consider the SRI question in more holistic terms rather than using the exclusionary format favored by most SRI funds. Investors seem to prefer to reward firms who display overall positive social behavior rather than to exclude firms on the basis of certain products or practices. These findings can help providers of SR investment vehicles to improve the SRI products that they offer to the general investor, thus both encouraging the initial adoption of SR criteria by investors and increasing overall investment in SR choices.
Keywords: Corporate Social Responsibility; Environment; Investor survey; Negative Screening; Socially Responsible Investing